Assessment of the Earth's Cold Plasmatrough Modeling by Using Van Allen Probes/EMFISIS and Arase/PWE Electron Density Data. Issue 12 (7th December 2021) - Botek, E.; Pierrard, V.; Darrouzet, F.
Abstract: The Space Weather Integrated Forecasting Framework (SWIFF) Plasmasphere Model (SPM) is a 3D kinetic model of the plasmasphere coupled to the ionosphere. This combined system has been routinely used to evaluate principally the plasmapause formation and evolution, and the plasmasphere's dynamics. The model contains analytical equations for the plasmasphere and plasmatrough regions that have been empirically determined using observations of satellite and ground‐based data. In the present work, a revision of the plasmatrough equations is proposed using electron density data from the Van Allen Probes mission and paying particular attention to the spatiotemporal variation as well as to geomagnetic activity influence. Comparisons are performed with other parametrizations and with electron density data from the Arase mission. This assessment demonstrates that the plasmatrough electron density was slightly underestimated with respect to the new observations, in particular for high L values ( L > 3) and high geomagnetic activity. In addition, the overall performance of the new parametrization follows a satisfactory general trend despite a large variability of density data observed in the plasmatrough. The plasmatrough is separated from the refilling zone in the model by considering vestigial and outer edge plasmapause positions. Key Points: Plasmatrough electron density equations in the SPM model are revisited with new parametrization using data from Van Allen Probes mission The new parametrized equations provide improved data for high L values ( L > 3) and high geomagnetic activity Refilling mechanisms through a thicker plasmasphere boundary layer must be taken into account for quiet periods after erosion